Dissection of the multiple sclerosis associated DR2 haplotype. - Etzensperger, R; McMahon, R; Jones, E; Fugger, L (2008)
Epidemiological and genetic data have consistently identified associations with HLA class II alleles in many autoimmune diseases. In multiple sclerosis (MS), an autoimmune disease targeting central nervous system (CNS) myelin, the DR2 haplotype (DRB1*1501, DRB5*0101 and DQB1*0602) remains the strongest identified genetic risk factor in Caucasians. However, it is hard to tease apart the precise contributions of its constituent individual alleles and their modes of action remain poorly understood, due in part to the strong linkage disequilibrium in this region. Recent work in humanized mice indicates functional epistatic interactions whereby DRB5*0101 directly modulates the severity of the ensuing disease through activation-induced cell death (AICD) of encephalitogenic T cells which are restricted by DRB1*1501. Complementary structural studies help to explain how these alleles may facilitate thymic escape of autoreactive T cells and contribute to peripheral T cell activation via suboptimal binding interactions and mechanisms of molecular mimicry. Here we discuss the emerging role of the constituent alleles of the DR2 haplotype and our ongoing efforts to uncover the mechanisms by which they influence MS pathogenesis.